2023
DOI: 10.3389/fendo.2022.1039494
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing and bioinformatic analyses revealed differences in gene mutation profiles in papillary thyroid cancer patients with and without benign thyroid goitre background

Abstract: BackgroundPapillary thyroid cancer (PTC) is the most common thyroid malignancy. Concurrent presence of cytomorphological benign thyroid goitre (BTG) and PTC lesion is often detected. Aberrant protein profiles were previously reported in patients with and without BTG cytomorphological background. This study aimed to evaluate gene mutation profiles to further understand the molecular mechanism underlying BTG, PTC without BTG background and PTC with BTG background.MethodsPatients were grouped according to the his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Previously, XIST had been observed to promote oncogenic activities in papillary thyroid carcinomas (PTC) [42]. Among genes highly targeted in males, tumor suppresor gene KDM6A is known to regulate multiple genes involved in immune response, suggesting its potential influence on the risks of developing various autoimmune conditions [43]; Among other genes highly targeted in males, PCM1 mutation has also been associated with PTC [44]; while mutation in KMT2C has been identified as a molecular marker for primary thyroid osteosarcoma [45]. Additionally, overexpression of SOS1 , which also showed higher targeting in males, have been found to promote cell proliferation and cell apoptosis in PTC cells [46].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, XIST had been observed to promote oncogenic activities in papillary thyroid carcinomas (PTC) [42]. Among genes highly targeted in males, tumor suppresor gene KDM6A is known to regulate multiple genes involved in immune response, suggesting its potential influence on the risks of developing various autoimmune conditions [43]; Among other genes highly targeted in males, PCM1 mutation has also been associated with PTC [44]; while mutation in KMT2C has been identified as a molecular marker for primary thyroid osteosarcoma [45]. Additionally, overexpression of SOS1 , which also showed higher targeting in males, have been found to promote cell proliferation and cell apoptosis in PTC cells [46].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies had reported significantly higher oxidative stress in a group of PTC patients compared to a group of BTG patients ( Erdamar et al, 2010 ; Ramli et al, 2017 ), suggesting the role of oxidative stress in PTC tumourigenesis. Furthermore, differences in gene alteration patterns had been detected between BTG and PTC patients ( Eng et al, 2023 ), providing insights into the molecular mechanisms underlying the benign-to-malignant transformation. However, studies evaluating and comparing oxidative stress and antioxidant capacity between benign and malignant thyroid lesions within the same patient are rarely performed.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of point mutations in DNA has been associated with its 8-oxoG content ( Kuchino et al, 1987 ; Ribeiro et al, 1994 ). DNA damage coupled with aberrant DNA repair-related pathways, has been suggested to initiate thyroid tumourigenesis and play a crucial role in PTC progression from BTG ( Ameziane El Hassani et al, 2019 ; Eng et al, 2023 ). OGG1 codes for 8-oxoguanine glycosylase (OGG1), which participates in the BER pathway for the mutagenic 8-oxoG ( Bruner et al, 2000 ; Izumi et al, 2003 ; Banerjee et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations